HIV & immune reconstitution inflammatory syndrome (IRIS) - Sharma, SurendraK; Soneja, Manish (Indian journal of medical research (New Delhi, India : 1994), 2011)
Antiretroviral therapy (ART) initiation in HIV-infected patients leads to recovery of CD4+T cell numbers and restoration of protective immune responses against a wide variety of pathogens, resulting in reduction in the frequency of opportunistic infections and prolonged survival. However, in a subset of patients, dysregulated immune response after initiation of ART leads to the phenomenon of immune reconstitution inflammatory syndrome (IRIS). The hallmark of the syndrome is paradoxical worsening of an existing infection or disease process or appearance of a new infection/disease process soon after initiation of therapy. The overall incidence of IRIS is unknown, but is dependent on the population studied and the burden of underlying opportunistic infections. The immunopathogenesis of the syndrome is unclear and appears to be result of unbalanced reconstitution of effector and regulatory T-cells, leading to exuberant inflammatory response in patients receiving ART. Biomarkers, including interferon-γ (INF-γ), tumour necrosis factor-α (TNF-α), C-reactive protein (CRP) and inter leukin (IL)-2, 6 and 7, are subject of intense investigation at present. The commonest forms of IRIS are associated with mycobacterial infections, fungi and herpes viruses. Majority of patients with IRIS have a self-limiting disease course. ART is usually continued and treatment for the associated condition optimized. The overall mortality associated with IRIS is low; however, patients with central nervous system involvement with raised intracranial pressures in cryptococcal and tubercular meningitis, and respiratory failure due to acute respiratory distress syndrome (ARDS) have poor prognosis and require aggressive management including corticosteroids. Paradigm shifts in management of HIV with earlier initiation of ART is expected to decrease the burden of IRIS in developed countries; however, with enhanced rollout of ART in recent years and the enormous burden of opportunistic infections in developing countries like India, IRIS is likely to remain an area of major concern.